A Rare Diagnosis of Parotid Gland Follicular Lymphoma Arising in Warthin Tumor: Case Report and Literature Review - Ido Vaknin; Irit Allon; Shirley Zafrir-Haver; Alex Abramson (Medicina)
Introduction: A Warthin tumor is a benign salivary gland neoplasm, mostly found in the parotid gland. The number of reported Warthin tumors has increased over the years due to better diagnostic modalities and health system modernization. Warthin tumor rarely transforms into a malignant tumor; in this work, we present all cases reported in the English literature of different types of lymphomas within Warthin tumors. In this case, we present a low-grade follicular lymphoma arising within a Warthin tumor. Clinical report: A 64-year-old man presented to an oral and maxillofacial surgery clinic with a growing right facial mass. The medical history was significant for stable angina pectoris, hypertension, hypercholesterolemia, obesity, and a 20-pack-year smoking history. Fine needle aspiration suggested a diagnosis of Warthin tumor. A contrast CT scan of the parotid gland demonstrated a 2.9 × 2.7 × 4.1 cm diameter mass. The patient underwent right superficial parotidectomy. Histological examination of the mass revealed a low-grade follicular lymphoma arising in a pre-existing Warthin tumor. The postoperative PET CT showed no distant disease, and bone marrow biopsy during hematologic evaluation confirmed Stage 1 low-grade follicular lymphoma. The patient received 24 Gy of VMAT radiation therapy to the right parotid gland and continued hematologic follow-up. Conclusions: Based on a literature review, this is one of the few well-documented cases reported of low-grade follicular lymphoma within a Warthin tumor. This case highlights the importance of the thorough evaluation and diagnosis of parotid masses. Furthermore, this case reopens the debate on the “wait and see” approach regarding Warthin tumors. Fine needle aspiration-based diagnosis should not be considered final, as some malignant characteristics can be missed if declining surgery.